CORPORATE SENTENCING IN A FORESTRY LAW BASED ON LEGAL PROTECTION AGAINST VICTIMS - RM. Armaya Mangkunegara (RechtIdee, 2018)
Corporate sentencing in a forestry law does not provide a model of settlement that accommodates the principle of corporate sentencing based on legal protection against the victim, thus requiring an academic breakthrough in the formulation of future legal provisions. The legal issue in this research is the concept of corporate sentencing in a forestry law based on legal protection against the victim. This research used statutary approach and conceptual approach. Legal protection of corporate forestry crime victims is a principle that needs to be prioritized. The legal protection of the victim is done in the form of reforestation of the principles of restorative justice, the principle of in dubio pro natura and the penalty of criminal type of restoration of forest condition.